THE EARLY CHILDHOOD EDUCATION AND THE MUNICIPAL PLAN OF EDUCATION OF MATAO (SP): THE COMPLIANCE WITH DEMAND AND INFRASTRUCTURE - Brandao, Carlos da Fonseca [UNESP]; Oliveira Trevelin, Fatima Gil de [UNESP]; Pissaia, Vitor Hugo [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2016)
This article analyzes the compliance with demand and the infrastructure conditions of the buildings of child education of the municipal system of Matao (SP) and compares it with the proposed for this education level in some aspects (offer, services and infrastructure) present in Municipal Plan of Education of Matao (SMEs 2003-2013). Finally, this work makes some observations about the current situation of the Child Education System. Then, it concludes that the general problems about Child Education in Matao are the same problems presented in a great part of Brazilian cities, especially the problem about the demand - this is larger than the number of vacancies available in Child Education (specially in nursery school).
Keywords: Child education; PME Municipal Plan of Education; The compliance with demand; Infrastructure